2017
DOI: 10.1016/j.immuni.2017.05.006
|View full text |Cite|
|
Sign up to set email alerts
|

Human Virus-Derived Small RNAs Can Confer Antiviral Immunity in Mammals

Abstract: RNA interference (RNAi) functions as a potent antiviral immunity in plants and invertebrates; however, whether RNAi plays antiviral roles in mammals remains unclear. Here, using human enterovirus 71 (HEV71) as a model, we showed HEV71 3A protein as an authentic viral suppressor of RNAi during viral infection. When the 3A-mediated RNAi suppression was impaired, the mutant HEV71 readily triggered the production of abundant HEV71-derived small RNAs with canonical siRNA properties in cells and mice. These virus-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(176 citation statements)
references
References 36 publications
5
170
1
Order By: Relevance
“…Further experimentation is therefore needed to address whether LGP2 acts in concert with other ISGs to suppress mammalian RNAi. The recent discovery that human enterovirus 71 encodes a VSR that interferes with Dicer activity to evade RNAi‐dependent restriction mechanisms (Qiu et al , 2017) opens up future avenues of research to assess the impact of LGP2 on mammalian antiviral RNAi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experimentation is therefore needed to address whether LGP2 acts in concert with other ISGs to suppress mammalian RNAi. The recent discovery that human enterovirus 71 encodes a VSR that interferes with Dicer activity to evade RNAi‐dependent restriction mechanisms (Qiu et al , 2017) opens up future avenues of research to assess the impact of LGP2 on mammalian antiviral RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…However, Dicer's catalytic function appears mainly confined to precursor microRNA (pre‐miRNA) processing, and its antiviral capacity in mammals remains much debated (Parameswaran et al , 2010; Cullen et al , 2013; Li et al , 2013, 2016; Maillard et al , 2013; Backes et al , 2014; Ding & Voinnet, 2014; Kennedy et al , 2015; Jeffrey et al , 2017; tenOever, 2017). Some studies have reported that RNAi can impact antiviral immunity in mammals during influenza A virus, hepatitis C virus, Nodamura virus and, more recently, human enterovirus 71 infection (Wang et al , 2006; Matskevich & Moelling, 2007; Li et al , 2013, 2016; Maillard et al , 2013; Qiu et al , 2017). In contrast, others have found low abundance of viRNAs in mammalian somatic cells infected with various viruses, and only a modest effect of Dicer deficiency on viral replication, suggesting that RNAi is not an active mechanism of antiviral defence in most mammalian cell types (Parameswaran et al , 2010; Girardi et al , 2013; Backes et al , 2014; Bogerd et al , 2014; Schuster et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian Dicer also takes part in antiviral immunity via a mechanism in which Dicer processes viral dsRNA precursors into siRNAs that suppresses viral activity. These viral-derived siRNAs were not detected until recently because the viruses have evolved strategies to counteract such antiviral immunity by suppressing RNAi [58][59][60][61].…”
Section: Dicer In Maintenance Of Genome Integritymentioning
confidence: 99%
“…In contrast to invertebrates, data supporting direct involvement of mammalian RNAi in antiviral defense are rather inconclusive. While a few studies suggested that RNAi could provide an effective antiviral response in ESCs and in mouse embryos Maillard et al, 2013;Qiu et al, 2017) other studies did not support that notion. For example, no siRNAs of viral origin have been found in human cells infected with a wide range of viruses (Pfeffer et al, 2005) or present siRNAs were not sufficient to mediate effective RNAi (Tsai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%